2022
DOI: 10.1007/s10072-022-06185-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex influences clinical phenotype in frontotemporal dementia

Abstract: Introduction Frontotemporal dementia (FTD) encompasses a wide spectrum of genetic, clinical, and histological findings. Sex is emerging as a potential biological variable influencing FTD heterogeneity; however, only a few studies explored this issue with nonconclusive results. Objective To estimate the role of sex in a single-center large cohort of FTD patients. Methods Five hundred thirty-one FTD patients were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…The FTD-MND subtype was a significant predictor of mortality [26]. Pengo et al [21] found that females exhibit a different progression of FTD compared to males. While males and females had similar survival duration and neurofilament levels, the authors suggested that since females live longer than males in general, that absence of differences in survival could indirectly mean that females have a more aggressive form of disease.…”
Section: Epidemiological and Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTD-MND subtype was a significant predictor of mortality [26]. Pengo et al [21] found that females exhibit a different progression of FTD compared to males. While males and females had similar survival duration and neurofilament levels, the authors suggested that since females live longer than males in general, that absence of differences in survival could indirectly mean that females have a more aggressive form of disease.…”
Section: Epidemiological and Clinical Studiesmentioning
confidence: 99%
“…The cognitive profile of people with bvAD identified less executive dysfunction compared to bvFTD but worse memory compared to typical AD. Sex may play a role in the clinical phenotype of FTD, with males being more likely to present with behavioural symptoms compared to females who were more likely to have cognitive impairment [21] as well as differences in the sex distribution of genetic vs. sporadic FTD [22]. In young-onset AD, there are also sex-specific differences.…”
Section: Epidemiological and Clinical Studiesmentioning
confidence: 99%
“…For example, our results suggest that AT may be more beneficial for female BDNF Val/Val carriers with executive dysfunction. Intriguingly, patients with Frontotemporal Dementia show impaired executive functions [ 55 ], which may be greater in female patients than male patients [ 56 ] despite similar disease prevalence in males and females [ 57 ]. Thus, exercise strategies should be tailored and personalized based on variables such as biological sex, genotype and cognitive domain showing impairment [ 6 , 7 ].…”
Section: Perspectives and Significancementioning
confidence: 99%
“…7 This could be explained by longer life expectancy in -7 of 10 females 30 and sex differences in phenotype and progression, with females having a more aggressive form of the different types of dementia. 30,31 Causes of death in HD were unsurprisingly attributed to HD and respiratory disorders. 13,32 Suicide is also a common cause of death in HD, 13,32 though we only had one individual with HD who had this as their reported cause of death.…”
Section: Cause Of Deathmentioning
confidence: 99%